1981
DOI: 10.1111/j.1399-0004.1981.tb01035.x
|View full text |Cite
|
Sign up to set email alerts
|

A boy with true hermaphroditism and sex chromosome mosaicism and a fertile woman with Turner mosaicism in a family with a translocation 8p:19p

Abstract: In a family with a balanced translocation t(8;19)(p21p13), there was a boy with true hermaphroditism and a karyotype 46, XX/46XY, t(8p;19p), and a woman with Turner mosaicism 46, XX, t(8p;19p)/45, X, t(8p;19p). Both of them had whole body chimerism, which in the boy and possibly also in the woman was due to the occurrence of double fertilization followed by fusion of the zygotes. The pathogenetic importance of the translocation for the development of these aberrations, and the clinical picture in the two patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…),t(1;22)(q32;q21) and t(8:19) (p21:p13), and no other family member was affected by sex chromosome abnormalities in two reports [9,10]. However, a boy with true hermaphroditism and 46,XX/46,XY mosaicism formed part of the family reported by Anneren et al [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…),t(1;22)(q32;q21) and t(8:19) (p21:p13), and no other family member was affected by sex chromosome abnormalities in two reports [9,10]. However, a boy with true hermaphroditism and 46,XX/46,XY mosaicism formed part of the family reported by Anneren et al [8]. …”
Section: Discussionmentioning
confidence: 99%
“…No other family members carried the translocation and sex chromosomal abnormality in these reports. There are three Turner syndrome patients with a familial balanced reciprocal translocation and monosomy of the X chromosome in the literature [8–10]. In these reports, the reciprocal translocations were t(2;22)(q?;q?…”
Section: Discussionmentioning
confidence: 99%
“…Normal fertility in women with 45,X could be explained by the presence of an additional normal cell line in their gonads or the absence of gonadal mosaicism. Annerén et al [18] reported that an elder mosaic Turner's syndrome woman, with a familial reciprocal translocation detected in lymphocytes and fibroblast, delivered 3 normally developed children and had not prior history of abortion. The latter cases showed family planning genetic counselling should be performed in a case-by-case basis.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of autosomal translocations and structural/numerical abnormalities of the X chromosome are a rarely reported, there are 12 cases published [9][10][11][12][13][14][15][16][17][18][19][20]. Here we describe a mosaic Turner syndrome patient with a maternally inherited reciprocal translocation with breakpoints at 2p13 and 12q24.…”
Section: Open Accessmentioning
confidence: 99%